2017
DOI: 10.1093/ejcts/ezw410
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of systemic vasoconstrictors on human pulmonary artery tension†

Abstract: This study demonstrated the efficacy and potency of clinically used vasopressors and endogenous vasopressors on human pulmonary vascular tone. PGF2a and KCl equally caused maximal amounts of constriction, whereas ET-1 had less effect and vasopressin had no effect. These effects may need to be taken into account in the clinical setting because they might result in the development of pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
1
10
0
3
Order By: Relevance
“…These data are in accord with recent studies of vasopressin in pulmonary hypertension that, while noting a vasopressin‐induced decrease in the pulmonary‐to‐systemic pressure ratio, ascribe this improvement to a rise in aortic pressure rather to pulmonary vasodilation . Vasopressin may be unique among pressors in having no pulmonary constrictor effect, but we concur that it has no apparent pulmonary vasodilator effect . Indirect vasodilation has been postulated, for example, through vasopressin‐induced release of atrial natriuretic peptide; but these effects would fall outside of the timeframe of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…These data are in accord with recent studies of vasopressin in pulmonary hypertension that, while noting a vasopressin‐induced decrease in the pulmonary‐to‐systemic pressure ratio, ascribe this improvement to a rise in aortic pressure rather to pulmonary vasodilation . Vasopressin may be unique among pressors in having no pulmonary constrictor effect, but we concur that it has no apparent pulmonary vasodilator effect . Indirect vasodilation has been postulated, for example, through vasopressin‐induced release of atrial natriuretic peptide; but these effects would fall outside of the timeframe of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Since 12 rings failed to contract to KCl, (37.6 mM [EC 80 ], calculated earlier [6]), they were eliminated from the study and the remaining 52 rings used. The effects of vasodilator agents on pulmonary artery tone (active tension to PGF 2α ) are summarised in Table 1 and …”
Section: Resultsmentioning
confidence: 99%
“…The vessels were then left to equilibrate with 21% O 2 : 5% CO 2 at 37˚C for 1 hour. PA rings were then pre-constricted with 11.21 µM PGF 2α (EC 80 ), calculated earlier from previous experiments [6]. When a stable active tension was achieved, a series of increasing concentration response curves were created for Sildenafil, Milrinone, Sodium Nitroprusside, Epoprostenol, Iloprost and Treprostinil by stepwise increases in agonist concentration in the myograph chamber when a plateau response was generated for the earlier concentration.…”
Section: Determination Of Agonist Induced Relaxationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulated Ca 2+ homeostasis, and increased Ca 2+ spark frequency promotes arrhythmogenesis of PV cardiomyocytes in HF, which may play an important role in the development of AF [19]. Interestingly, in vitro and in vivo studies showed that AVP produces relatively less vasoconstriction in pulmonary circulation [20, 21]. However, the role of AVP in PV arrhythmogenesis was not clear.…”
Section: Introductionmentioning
confidence: 99%